Bisphosphates for Osteoporosis: A Bibliometric Analysis of the Most Cited Articles. (18th May 2022) - Zhang, Yu; Hu, Man; Zhu, Lei; Wang, Junwu; Wang, Pingchuan; Shi, Pengzhi; Zhao, Wenjie; Liu, Xin; Peng, Qing; Meng, Bo; Chen, Chen; Feng, Xinmin; et al.
Abstract : Osteoporosis has become a major public health problem and bisphosphates treatment for osteoporosis is a rapidly developing research field. Every year, plenty of studies devoted to the treatment of osteoporosis are published, giving clinicians a new perspective on bisphosphates treatment for osteoporosis. However, the quality of the scientific papers in this area is unclear. The aim of the present study was to characterize the 100 top-cited articles regarding bisphosphates treatment for osteoporosis. This analysis provides an accessible list for practitioners of endocrinology, pharmacy, epidemiology, imaging, surgery, and scientific research to identify the most frequently cited literature and better understand the future direction.